2014
DOI: 10.1016/j.ttbdis.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Borrelia species in questing Gulf Coast ticks, Amblyomma maculatum

Abstract: Borrelia spp. are agents of Lyme disease and relapsing fever, diseases which use Ixodes hard ticks and Ornithodoros soft ticks, respectively, as primary vectors. Some relapsing fever spirochetes, such as B. miyamotoi, are also found in hard ticks. To date, no Borrelia sp. is known to use the hard tick, Amblyomma maculatum, as a vector. However, both B. burgdorferi and B. lonestari were recently detected in A. maculatum removed from hosts. In our study, DNA extracts from 306 questing adult A. maculatum collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
11
0
4
Order By: Relevance
“…However, in the phylogenetic tree presented by Margos et al [7], which includes B. turcica and other related reptile-associated strains of Borreliaceae without taxonomic standing, these species/strains exhibit the same pattern of branching as described by Takano et al [8], which was acknowledged by Adeolu and Gupta [4]. It should be noted, however, that in other recent studies [9,10], the position of the reptile-associated Borrelia species with respect to its branching position was found to be variable. Thus, further studies based on whole genome data are needed to clarify the position of B. turcica and the 'reptile group' of strains.…”
Section: Genomic Evidence For the Cohesiveness Of The Family Borreliamentioning
confidence: 76%
“…However, in the phylogenetic tree presented by Margos et al [7], which includes B. turcica and other related reptile-associated strains of Borreliaceae without taxonomic standing, these species/strains exhibit the same pattern of branching as described by Takano et al [8], which was acknowledged by Adeolu and Gupta [4]. It should be noted, however, that in other recent studies [9,10], the position of the reptile-associated Borrelia species with respect to its branching position was found to be variable. Thus, further studies based on whole genome data are needed to clarify the position of B. turcica and the 'reptile group' of strains.…”
Section: Genomic Evidence For the Cohesiveness Of The Family Borreliamentioning
confidence: 76%
“…identified in Amblyomma maculatum ticks from Texas in this study (box) and from Mississippi ( 12 ) shares a closer phylogenetic relationship to B. turcica than to to other Borreliae groups. Analysis is based on flaB sequences (267 bp).…”
Section: The Studymentioning
confidence: 51%
“…(accession no. KF395230) previously found in A. maculatum ticks in Mississippi and known to share a phylogenetic clade with B. turcica ( 12 ). Borrelia 16S rDNA primers produced nonspecific amplification with these 2 samples.…”
Section: The Studymentioning
confidence: 90%
See 1 more Smart Citation
“…Phylogenetic analysis of these Borrelia taxa has revealed that they are deeply divergent from both the Lyme disease-associated clade and those causing relapsing fever, justifying their inclusion as a separate cluster within the over-arching genus of Borrelia [50,51]. Intriguingly, these presumed reptile-associated species have subsequently been detected in Amblyomma maculatum collected in the Gulf Coast [52]. Similarly, related Borrelia have been detected in Amblyomma varanense collected from pythons in Thailand [53].…”
Section: The Non-conformist Third Borrelial Clustermentioning
confidence: 99%